2001
DOI: 10.1055/s-2001-14659
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of a Highly Effective Chiral Dipyridylphosphine Ligand and Its Application in the Ru-Catalyzed Asymmetric Hydrogenation of β-Ketoesters

Abstract: Abstract:A new chiral dipyridylphosphine ligand Tol-P-Phos has been synthesized and the structure of the complex of (R)-Tol-PPhos oxide with (-)-dibenzoyl-L-tartaric acid [(-)-DBT] was determined by single crystal X-ray diffraction. The ruthenium complex of Tol-P-Phos, Ru(R-Tol-P-Phos)(C 6 H 6 )Cl 2 , has been found to be a highly active and enantioselective catalyst in the asymmetric hydrogenation of b-ketoesters (up to 98.2% e.e.). The catalyst is also found to be air-stable even in solution.Key words: asymm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Our previous studies on catalytic asymmetric hydrogenation reactions demonstrated that the dipyridylphosphine ligands possessed better air stability than that of 2,2Ј-bis(diphenyllphosphino)-1,1Ј-binaphthyl (47,48). In the present air-accelerated system, air is one of the key factors for the enhancement of reaction rates, and consequently, dipyridylphosphines with good air stability exhibited extraordinary advantages to other common diphosphines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies on catalytic asymmetric hydrogenation reactions demonstrated that the dipyridylphosphine ligands possessed better air stability than that of 2,2Ј-bis(diphenyllphosphino)-1,1Ј-binaphthyl (47,48). In the present air-accelerated system, air is one of the key factors for the enhancement of reaction rates, and consequently, dipyridylphosphines with good air stability exhibited extraordinary advantages to other common diphosphines.…”
Section: Resultsmentioning
confidence: 99%
“…48) for Ru-catalyzed hydrogenation of a broad scope of simple ketones (17,18). Particularly noteworthy was the observation that the Ru-(P-Phos) catalyst system was highly air-stable even in solution (18,47,48). Capitalizing on this fact, we conjectured that the air stability of P-Phos-type ligands might be especially favorable for the air-accelerated, copper(II)-catalyzed asymmetric hydrosilylations of unfunctional ketones (45).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, higher temperature (100°C) led to excellent chiral efficiency (97% ee) under 100 atm H 2 pressure. 23 In contrast, the employment of Ru complexes of P-Phos 11b or Tol-P-Phos 12 applied to the practical synthesis of L-carnitine (Scheme 6), an important agent responsible for the transport of long-chain fatty acid through human metabolism. 23 Activity and Air Stability of the Ru-(P-Phos) Catalyst System.…”
Section: Scheme 3 Hydrogenation Of 2-(6′-methoxy-2′-naphthyl)propenoicmentioning
confidence: 96%
“…The small dihedral angle of the SEGPHOSRu complex (658) may have a major influence on the high enantioselectivity. MeO-BIPHEP [14 q, 18], Tol-P-Phos [43], 2A [25], ferrocenyl diphosphine 2Bc [44], and the monodentate phosphine 1C [31] also show high enantioselectivity. A Ru complex with the diphosphinite ligand Xylyl-o-BINAPO gives the hydroxy ester in 99% ee [35].…”
Section: B-keto Estersmentioning
confidence: 99%